PERAN UNSUR KOMUNIKASI TERAPEUTIK DALAM MENINGKATKAN KUALITAS ASUHAN KEPERAWATAN - Artanti Laili Zulaiha; Alief Budiyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Therapeutic communication is an essential competency in nursing practice because it serves as a professional medium to build a trusting relationship between nurses and patients. Effective communication does not solely convey clinical information, but also acts as a psychosocial intervention that affects the patient's emotional state, attitude, and involvement in the treatment process. This article aims to examine the concept of therapeutic communication, identify its constituent elements, and explain its application in nursing practice. The method used is a literature study by studying relevant textbooks and journal articles. The results of the study show that therapeutic communication consists of elements of communicators, communicators, messages, media, effects, feedback, environment, and disturbances. The optimization of these elements has been proven to contribute to increasing patient satisfaction, reducing anxiety, and strengthening the quality of holistic and human-value-oriented nursing care.